Strengthening Islamic Education Management: Policy Implementation and Strategic Contributions - Prima, Anggra; Masruhim, Muh. Amir; Abdunnur, Abdunnur; Komariyah, Laili (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study aims to describe the implementation of policies, analyze decision-making mechanisms, and describe their contribution to the development strategy of the Islamic Education Management Study Program (MPI) at STAI Sangatta, East Kutai. The research used a descriptive qualitative approach. Study program leaders, lecturers, educational staff, and students were selected through purposive sampling. Data were collected using semi-structured interviews, participant observation, and document analysis. The Miles and Huberman interactive model was used to process the data. The findings indicate that policy implementation has been incorporated in the curriculum, academic activities, research, and community service. However, limited resources have constrained its effectiveness. Decision-making is done through lecturer meetings and deliberation forums. Yet, participation is unequal due to leadership dominance and low student involvement. Consistent policy implementation and participatory decision-making have contributed significantly to the development strategy of the MPI Study Program. These efforts have strengthened curriculum alignment, enhanced lecturer competence, and expanded research and community engagement initiatives. However, their impact has not yet been optimal due to limited human resources and unequal participation in decision-making. The findings suggest that the success of the study program's development strategy depends on the integration of effective policy implementation with inclusive governance practices that ensure shared responsibility, transparency, and sustainable academic improvement.